The Analysis of Depression Levels at Undergraduate Students - Fitri Fahri Anti; Meri Haryani; Hera Wahyuni (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
An Analysis of Depression Levels in Undergraduate Students during the Covid-19 Pandemic. At this time there are not a few events cause psychological reactions that trigger emotional stress such as anxiety, worried, decreased interest in social activities, withdrawal from the environment and personal. The purpose of this study was to determine the level of depression in undergraduate students and this study used quantitative research with a descriptive analytics approach. The sample in this study amounted to 112 undergraduate students at Jambi University. The research instrument used the Beck Depression Inventory II (BDI-II) questionnaire that has been adapted by Dina, the data collected used univariate analysis with frequency distribution. The results of the study, 26.8% of students experienced mild depression, 20.5% had moderate depression and 7.1% severe depression. This case indicated that during the covid-19 pandemic undergraduate students who are completing the final task (thesis) experienced mild depression.